The structure of social relations in the community: An empirical analysis for achieving social and economic inclusion - Aubrey D. Tabuga; Carlos C. Cabaero (Philippine Institute for Development Studies (PIDS), 2020)
Achieving inclusive development has become the mantra in the global and national development discourse. A great deal of the initiatives towards inclusive development entails redistributive efforts such as the provision of social protection for the poor. But the conditions of the poor may not be characterized only by their limited economic means and low level of skills but also their tendency to be socially excluded from others from whom they can obtain information on services and opportunities that can help them improve their well-being. Poverty and social exclusion, if not isolation, form a vicious cycle wherein the poor are often excluded because their lack of means limit them from extending their reach to others, and this exclusion in turn enforces their dire condition because they are unable to learn new and better opportunities. This paper examines the extent of social deprivation, if any, among the poor and other segments of the community. Specifically, it aims to illustrate the characteristics of social networks that poor families have through social network analysis (SNA). It inquires on the questions - How are the poor situated within the community network? Are they isolated, excluded, or integrated? To examine social inclusion or exclusion, this study uses social relations data (i.e. kinship and friendship ties) gathered in 2016 on all households residing in a rural, fishing village in the Philippines. Its primary objective is to draw insights for developing or improving efforts towards social and economic inclusion of the poor.
Keywords: 330; Social network analysis; social inclusion; social exclusion; inclusive development; Philippines